Compressive strength and the effect of duration after photo-activation among dual-cure bulk fill composite core materials - Alkhudhairy, Fahad (Pak J Med Sci, 2016)
OBJECTIVES: To assess compressive strength and effect of duration after photoactivation on the compressive strength of different dual cure bulk fill composites. METHODS: Seventy-two disc shaped (4x10mm) specimens were prepared from three dual cure bulk fill materials, ZirconCore (ZC) (n=24), MulticCore Flow (MC) (n=24) and Luxacore Dual (LC) (n=24). Half of the specimens in each material were tested for failure loads after one hour [MC1 (n=12), LC1 (n=12) & ZC1 (n=12)] and the other half in 7 days [MC7 (n=12), LC7 (n=12), ZC7 (n=12)] from photo-polymerization using the universal testing machine at a cross-head speed of 0.5 cm/minutes. Compressive strength was calculated using the formula UCS=4f/πd(2). Compressive strengths among different groups were compared using analysis of variance (ANOVA) and Tukey’s multiple comparisons test. RESULTS: Maximum and minimum compressive strengths were observed in ZC7 (344.14±19.22) and LC1 (202.80±15.52) groups. Specimens in LC1 [202.80 (15.52)] showed significantly lower compressive strength as compared to MC1 [287.06 (15.03)] (p<0.01) and ZC1 [276.82 (11.51)] (p<0.01). ZC7 [344.14 (19.22)] specimens showed significantly higher (p<0.01) compressive strengths compared to LC7 [324.56 (19.47)] and MC7 [315.26 (12.36)]. Compressive strengths among all three materials were significantly higher (p<0.01) at 7 days as compared to one hour. CONCLUSIONS: Bulk fill material with Zr nano-hybrid filler (ZC) showed high compressive strength compared to MC and LC. Increasing the post photo-activation duration (from one hour to 7 days) significantly improves the compressive strengths of dual cure bulk fill material.